Using absorbance as a measure of turbidity in highly caustic solutions - Radomirovic, Tomoko; Smith, P.; Jones, Franca (Elsevier, 2013)
This note shows that the dissolution of kaolin and its subsequent re-crystallization as DSP can be monitored using a simple UV–vis method that measures the turbidity of the system. The method is shown to be accurate, reproducible and sensitive. The dissolution of kaolin can be accurately determined by way of a solids calibration curve and this is supported by simultaneous measurements of the dissolved silicate by an inductively coupled plasma (ICP) technique. Additionally, turbidity is often used to measure induction times of nucleation thus the method can monitor dissolution and nucleation simultaneously. It must be remembered, however, that turbidity will show different behaviour to ICP when phenomena such as settling and aggregation occur thus these processes must be considered when interpreting data. Finally, the size limit of the turbidimetric technique must be determined as this, too, can influence the interpretation of data.